Trees for global benefit program: Environmental Conservation Trust (ECOTRUST) of Uganda - Masiga, Moses; Mwima, P.; Kiguli, Lillian (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Case study for the report "Institutional innovations in African smallholder carbon projects" available at http://hdl.handle.net/10568/21222